Designing Management of Teaching Factory Based on Activity Strategy In Era 4.0 (Case study at SMK Bustanul Falah Banyuwangi) - Huda, Nurul; Usriyah, Lailatul (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2022)
Provision of skilled human resources can be realized through Vocational High School. Graduates from the school are expected to be ready to use in the ASEAN workforce and have an entrepreneurial character trait. One of the efforts to produce graduates is the application of teaching factory, where management is needed. The purpose of this study was to determine (1)management in teaching factory terms of: planning, organizing, implementing, monitoring and evaluating; (2) find out the active strategy in IR 4.0; (3) knowing themanagement teaching factory active strategy in IR 4.0 at SMK Bustanul Falah Banyuwangi. This research is a qualitative research with data collection techniques including interviews, observation and documentation analysis. Data analysis techniques using qualitative descriptive analysis including data collection, data reduction, data display and data verification. The results of this study: (1)management teaching factory at SMK Bustanul Falah Banyuwangi in terms of (a) planning, (b) organizing, (c) implementation, and (d) supervision is done well and integrated by all school components. (2) active learning strategies have been implemented well (a) learning prioritizes student competencies, (b) teachers as facilitators guiding in the learning experience process, (c) Developing industry-based learning. (3) the results of themanagement design teaching factory provide provisions for the industry, and the output is well absorbed by the industry.